Novel compact microstrip ultra-wideband filter utilizing short-circuited stubs with less vias - Mohammad Shahrazel, Razalli; Alyani, Ismail; Mohamed Adzir, Mahdi (EMW Publishing, 2009)
Full text of this article is also available at http://ceta.mit.edu/PIER/